Probabilistic mesoscale analysis of concrete beams subjected to flexure - Al-Jelawy, Haider M.; Al-Rumaithi, Ayad; Fadhil, Aqeel T.; Al-Sherrawi, Mohannad H. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the probabilistic behavior of plain concrete beams subjected to flexure is studied using a continuous mesoscale model. The model is two-dimensional where aggregate and mortar are treated as separate constituents having their own characteristic properties. The aggregate is represented as ellipses and generated under prescribed grading curves.
Keywords: concrete beam; flexure; grading curve; mesoscale; probabilistic analysis; uncertainty